O efeito do ambiente na distribuição e no processo de diversificação de camarões do gênero Macrobrachium - Morais, Amanda Franco de (2023)
Through phylogenetic and geographic approaches, ecologists and biogeographers have sought to understand the processes that shape diversity. Shrimp of the genus Macrobrachium, belonging to the Palaemonidae family, have a wide global distribution in freshwater and estuarine environments. The diverse reproductive strategies of these species contribute to their success in conquering coastal and continental systems, both tropical and temperate. Due to their complex biology, wide geographic distribution and habitat diversity, shrimps of the genus Macrobrachium are an ideal group to explore the relationship between niche evolution and diversification processes. Divided into two chapters, the first explored different hypotheses about the role of the environment in the global distribution of species richness of the genus Macrobrachium. In the second chapter, an evaluation of the niche evolution and speciation patterns of Macrobrachium species in the Americas region was carried out.